Armed conflicts, 1946–2013. (July 2014) - Themnér, Lotta; Wallensteen, Peter
In 2013, the Uppsala Conflict Data Program (UCDP) recorded 33 armed conflicts with a minimum of 25 battle-related deaths, up by one from 2012. Seven of these were recorded as wars, that is conflicts leading to 1, 000 or more battle-related deaths in a calendar year. There have been 144 armed conflicts (47 wars) since 1989 and 254 armed conflicts (114 wars) since 1946. For the past ten years the amount of active armed conflict has fluctuated between 31 and 37. Six peace agreements were signed during the year 2013, two more than in the previous year. For the first time, this article also provides data on trends in battle-related deaths since 1989. These data do not show a clear time-trend. However, there is a particular difficulty in mapping the conflict in Syria, for which no credible battle-related deaths in 2013 can yet be reported.